Helminthosporium Leaf Spot - Monica L. Elliott; Philip F. Harmon (EDIS, 2011)
This fungal disease is most serious on bermudagrass and acts over a wide range of temperatures. This revised 2-page fact sheet was written by M. L. Elliott and P. F. Harmon, and published by the UF Department of Plant Pathology, February 2011.